2019
DOI: 10.2144/fsoa-2019-0076
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Serum Levels of IL-18 and Soluble IL-2 Receptor on the Clinical Outcome of Patients With Diffuse Large B-cell Lymphoma Treated with R-CHOP Regimen

Abstract: Aim & methods: To assess the impact of pretreatment serum levels of IL-18 and soluble IL-2 receptor (sIL-2R) on the clinical outcome of patients with diffuse large B-cell lymphoma treated with an R-CHOP protocol. Total 73 patients were included. Results: Elevated serum IL-18 (using mean as cutoff) was associated with numerically lower complete remission, and 3-year disease-free survival rates; however, the difference was not statistically significant. Nevertheless, the 3-year overall survival rates were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Several studies assessed IL-18 mRNA and protein expression in lymphoma patients either in serum or the affected tissues. For DLBCL, increased serum IL-18 was correlated with lower CR rates after treatment and decreased OS and DFS [83][84][85], while higher IL-18 tissue expression was characteristic of the more aggressive non-GCB DLBCL subtype [86]. In patients with SS-associated MALT lymphomas, increased IL-18 mRNA levels in affected SGs were documented compared to SS patients without lymphoma, with higher IL-18 also correlating with the presence of GC-like structures [89].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies assessed IL-18 mRNA and protein expression in lymphoma patients either in serum or the affected tissues. For DLBCL, increased serum IL-18 was correlated with lower CR rates after treatment and decreased OS and DFS [83][84][85], while higher IL-18 tissue expression was characteristic of the more aggressive non-GCB DLBCL subtype [86]. In patients with SS-associated MALT lymphomas, increased IL-18 mRNA levels in affected SGs were documented compared to SS patients without lymphoma, with higher IL-18 also correlating with the presence of GC-like structures [89].…”
Section: Discussionmentioning
confidence: 95%
“…The impact of pretreatment IL-18 serum levels on the outcome of DLBCL patients receiving Rituximab-CHOP was investigated by Khaled et al The authors reported that CR and 3-year disease-free survival (DFS) rates were lower for patients with increased IL-18 serum levels, though the difference was not statistically significant. Nevertheless, the 3-year OS rates were significantly more favorable for the group with a lower IL-18 serum level [85]. Using tissue microarrays, Lu et al highlighted that higher IL-18 expression was detected in DLBCLs with non-germinal center B cell-like (GCB) phenotype compared to those with GCB phenotype [86].…”
Section: The Nlrp3 Inflammasome In Lymphomagenesismentioning
confidence: 99%